The Influence of Agility, Speed and Coordination to Dribbling Ability of Soccer PS. UIR Pekanbaru - Oca Fernandes AF; Donie; Roma Irawan (Fakultas Ilmu Pendidikan UNP)
The problem in this study when athletes do dribbling is still not good, this is seen when athletes do dribbling, the ball often out of control when doing dribbling This type of research is quantitative with causal associative causal correlation approach to know the direct, indirect and simultaneous effect of agility (X1), velocity (X2), eye-foot coordination (X3) on dribbling ball (Y). . Data were collected using Dodging Run tests for agility, run 30 meters for speed, Soccer Volley Test-Modified for eye-toe coordination and Dribbling Ball for dribbling ability. The result of data analysis showed that normal path coefficient value, significant and linear, (1) There is significant direct influence Agility of Dribbling with big influence 12,89%. (2) There is a significant direct influence Speed to Dribbling ability with big influence 9,42%. (3) There is a significant direct influence of foot-eye coordination on Dribbling ability with a large influence of 11.22%. (4) There is indirect influence Agility on Dribbling ability through Eye-foot Coordination with big influence 22.18%. (5) There is indirect effect Speed to Dribbling ability through Eye-foot Coordination with big influence 24,40%. (6) There is simultaneous influence Agility, Speed and Eye-foot Coordination of Dribbling ability with a large influence of 71.75%.